The Likelihood Of Fraudulent Financial Reporting Among Listed Companies In Nigeria: Application Of The Fraud Triangle Theory - Murumba, Inekwe (2021)
The objective of this study is to investigate the likelihood of fraudulent financial reporting among the listed companies in Nigeria. Using several proxies of the fraud triangle theory: liquidity, profitability, and financial distress (pressure elements); auditor firm size, audit fees, auditor firm size-audit fees interaction, and corporate social responsibility (opportunity elements); earnings management, and earnings management-audit fees interaction (rationalisation elements), this study test whether the identified variables are related to fraudulent financial reporting in Nigeria. Using a dataset of 516 firm-year observations of non-financial listed companies on the Nigerian stock exchange from 2013 to 2018, the study uses Benford’s law of first digit to categorise the companies into fraudulent and non-fraudulent firms. From the multivariate logistic regression analyses of the data, the study finds that liquidity and profitability as pressure elements are significantly related to fraudulent financial reporting. However, while profitability exerts a negative relationship, liquidity provides support for a positive relationship. Among the proxies of opportunity element, the audit fee has a significant negative relationship with fraudulent financial reporting. In respect of the rationalisation element, the audit fee moderates the relationship between earnings management and fraudulent financial reporting. The results have implications for early detection and prevention of fraudulent financial reporting in Nigeria. The findings in this study could also encourage regulatory authorities to review the audit fee differences between the Big 4 audit firms and the non-Big 4 audit firms in an effort to minimise the incidence of fraudulent financial reporting in Nigeria. Finally, the outcomes of several additional and robustness tests performed support the primary findings of this study.